Report on the mineral resources of the island [electronic resource] - Howley, James P., 1847-1918.; Newfoundland. Geological Survey. ([St. John's, Nfld. : s.n.], 1917)
Tables. Cover title: Report upon the mineral resources of the island. At head of title: Geological Survey of Newfoundland. "For the year 1903." Electronic reproduction. Mode of access: Internet. 44